Biographical Entanglements, Self-Reflexivity, and Transnational Knowledge Production. (November 2016) - Ruokonen-Engler, Minna-Kristiina; Siouti, Irini
The critique of methodological nationalism in the social sciences has posed a theoretical and methodological challenge to qualitative social research. It has forced researchers to reflect on the possibilities and limitations of applying qualitative research methods in their research on transnational social phenomena. We underline the need to examine the influence of the biographical experiences of the researcher on the research process in transnational research settings. We argue that by inducing biographical self-reflection during the research process, it is possible to work out the possible biographical entanglements with the research topic and to reflect their influence on the further development of the research process. In consequence, it is possible to tackle methodologically the "invisible" role of the researcher in the narrative construction of transnational social fields and to show how transnational knowledge production is an intersubjective, relational activity.